Polysaccharides from Passion Fruit Peels: From an Agroindustrial By-Product to a Viable Option for 5-FU-Induced Intestinal Damage - Karien Sauruk da Silva; Kahlile Youssef Abboud; Carolina Silva Schiebel; Natalia Mulinari Turin de Oliveira; Laryssa Regis Bueno; Lara Luisa Valerio de Mello Braga; Bruna Carla da Silveira; Isabella Wzorek França dos Santos; Everton dos Santos Gomes; Marcelo Biondaro Gois; Lucimara Mach Côrtes Cordeiro; Daniele Maria Ferreira (Pharmaceuticals, 2023)
Gastrointestinal mucositis is a serious and dose-limiting toxic side effect of oncologic treatment. Interruption of cancer treatment due to gastrointestinal mucositis leads to a significant decrease in cure rates and consequently to the deterioration of a patient’s quality of life. Natural polysaccharides show a variety of beneficial effects, including a gastroprotective effect. Treatment with soluble dietary fiber (SDF) from yellow passion fruit (Passiflora edulis) biomass residues protected the gastric and intestinal mucosa in models of gastrointestinal injury. In this study, we investigated the protective therapeutic effect of SDF on 5-FU-induced mucositis in male and female mice. Oral treatment of the animals with SDF did not prevent weight loss but reduced the disease activity index and preserved normal intestinal function by alleviating diarrhea and altered gastrointestinal transit. SDF preserved the length of the colon and histological damage caused by 5-FU. SDF significantly restored the oxidative stress and inflammation in the intestine and the enlargement and swelling of the spleen induced by 5-FU. In conclusion, SDF may be a promising adjuvant strategy for the prevention and treatment of intestinal mucositis induced by 5-FU.